Development of work and energy encyclopedia based on science technology society - ., Mujadi; Budi, A S; I M Astra, Z Zulkarnain, (Opción, 2019)
This study aims to develop work and energy encyclopedias based on Science Technology Society (STS), that is suitable for use as a source of learning. The method that used in this research is Research and Development (R&D) with the ADDIE model. ADDIE is an acronym of Analysis, Design, Development, Implementation, and Evaluation. As a result, the encyclopedia developed based on scientific approach can improve high school students’ learning outcomes. In conclusion, the work and energy encyclopedia that was developed based on Science, Technology, and Society (STS) is feasible to be used as a learning resource in physics subject.